Effect of bluetongue serotype 3 vaccines on probability of viremia and NSAID usage in Dutch dairy cattle herds - Everts, Reinard R.; Groenevelt, Margit; Oosterhuis, Kees-Jan; Kelderman, Elske; Koop, Gerrit (Frontiers in Veterinary Science, 2025)
IntroductionAfter the outbreak of bluetongue serotype 3 (BTV3) in The Netherlands in September 2023, three pharmaceutical companies developed inactivated vaccines against this newly emerged serotype in a short period of time, making it possible to start a vaccination campaign just before the start of the new outbreak in 2024. This study describes effectiveness of these vaccines under field conditions in Dutch dairy cattle herds.Materials and methodsData from 1,114 dairy cattle herds was collected, of which 518 (46.5%) completed the double vaccination scheme and 29 (2,6%) vaccinated once. Results from PCR blood samples that were taken as part of the early warning system were used as a proxy for viremia. As a proxy for morbidity in dairy cattle herds, NSAID usage was used.ResultsHerds that fully vaccinated with Bultavo, were less frequently tested for BTV3 and we observed a significant reduction in the probability of detecting bluetongue virus RNA compared to non-vaccinated herds. A significant increase in NSAID usage in the months July, August, September compared to the same period the year before was seen in non-vaccinated herds. Such increase was also seen in vaccinating herds, but a significantly smaller increase was seen for Bultavo vaccinating herds.DiscussionAltogether, we found large differences between the three vaccines in field effectiveness in dairy cattle in 2024 and conclude that Bultavo is the preferable option to prevent clinical signs and disease transmission under these circumstances.